2017
DOI: 10.1177/0193945917704201
|View full text |Cite
|
Sign up to set email alerts
|

The Identity Threat of Weight Stigma in Adolescents

Abstract: Obesity remains a serious public health issue in adolescents, who may be subjected to weight stigma leading to increased stress and poor health outcomes. Stigma can be detrimental to adolescents during self-identity formation. The purpose of this study was to examine weight stigma in adolescents in light of the Identity Threat Model of Stigma. A cross-sectional correlational design was used to examine the relationships among the variables of weight stigma, psychosocial stress, coping styles, disordered eating,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 32 publications
(50 reference statements)
1
33
0
Order By: Relevance
“…Body image has always been an important part of societies and cultures, and overweight or obese individuals are frequently subject to weight-related stigma, either through the media or through bullying [53,54]. Among adolescents, weightrelated stigma is reported to be one of the most prevalent forms of bullying at school [55,56]. Only a few adolescents in this study stated that they had been bullied.…”
Section: Discussionmentioning
confidence: 62%
“…Body image has always been an important part of societies and cultures, and overweight or obese individuals are frequently subject to weight-related stigma, either through the media or through bullying [53,54]. Among adolescents, weightrelated stigma is reported to be one of the most prevalent forms of bullying at school [55,56]. Only a few adolescents in this study stated that they had been bullied.…”
Section: Discussionmentioning
confidence: 62%
“…Adolescents who become obese tend to be considered physically unattractive (Ehlert, Marston, Fontana, & Waldron, 2015; Zeller et al, 2008). Weight stigmatization and discrimination (Hand et al, 2017; Puhl & Heuer, 2010), weight-based teasing, and bullying (Ehlert et al, 2015; Janssen, Craig, Boyce, & Pickett, 2004) are common among adolescents. Therefore, adolescents are less likely to make friends with their peers who are obese or becoming obese.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, being overweight or obese is not an ideal physical feature for Taiwanese people. Previous studies have found that overweight and obese adolescents are at higher risk of weight stigmatization and discrimination than their normal-weight peers (Hand, Robinson, Stewart, Zhang, & Hand, 2017; Myers & Rosen, 1999; Puhl & Heuer, 2009, 2010; Smolak, Levine, & Thompson, 2001). Overweight and obese Taiwanese adolescents were also at a greater risk of weight stigmatization and discrimination among peers (Yen, Liu, Ko, Wu, & Cheng, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Body image has always been an important part of societies and cultures, and overweight or obese individuals are frequently subject to weightrelated stigma, either through the media or through bullying [55,56]. Among adolescents, weight-related stigma is reported to be one of the most prevalent forms of bullying at school [57,58]. Only a few adolescents in this study stated that they had been bullied.…”
Section: Discussionmentioning
confidence: 62%